Pencapaian Indikator Kinerja Utama Perguruan Tinggi Melalui KKN-MBKM Membangun Desa - Isnanto, Isnanto (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2024)
Project Based Learning (PjBL) model is a model launched by the Ministry of Education and Culture. The research that has been carried out has produced products in the form of 3 books entitled: Project Based Learning on thematic learning in elementary schools in grades IV, V and VI. For this reason, through this KKN-MBKM activity, a trial was carried out at the school where the KKN-MBKM was held. Students involved in teaching at school relate to the contents of textbooks and also other activities that support the converted courses. The results of these activities are in the form of activity implementation documents such as evaluation results data, student questionnaire results data, observation data and also photos and videos of the learning process. This data will later be processed independently into a research report. Conclusions from the implementation of KKN-MBKM in the Social Village, Paguyaman District, Boalemo Regency, Gorontalo Province, carried out 3 (three) main activities, namely: (1) Initial observations in the Social Village and at SDN 3 Paguyaman, SDN 4 Paguyaman and MI Fastabiqull Khairat Paguyaman; (2) Implementation of the core program in the form of project based learning in classes IV, V and IV at SDN 3 Paguyaman, SDN 4 Paguyaman and MI Fastabiqull Khairat Paguyaman; (3) Implementation of additional program activities in the form of: morning exercise together providing IT training to teachers at SDN 03 Paguyaman, gymnastics with village officials, mobile legend tournament activities, Free Fire Tournament, village Trofeo cup soccer, Prom Night activities, involvement in August 17 celebration, community service at the Social Village Office, community service at tourist attractions, attending the Fastabiqul Khairat ta'lim assembly, assisting with administrative activities at the Social Village Office; (4) The KKN-MBKM village development that has been carried out can increase the Main Performance Indicators (MPI) of Gorontalo State University, namely in the form of MPI 2 (students learn outside of campus), MPI 5 (publication/application of lecturer research), and MPI 6 (department partnerships).